Feeling Race: Theorizing the Racial Economy of Emotions - Bonilla-Silva, Eduardo (American Sociological Review, 2019)
In this presidential address, I advance a theoretical sketch on racialized emotions—the emotions specific to racialized societies. These emotions are central to the racial edifice of societies, thus, analysts and policymakers should understand their collective nature, be aware of how they function, and appreciate the existence of variability among emoting racial subjects. Clarity on these matters is key for developing an effective affective politics to challenge any racial order. After the sketch, I offer potential strategies to retool our racial emotive order as well as our racial selves. I end my address urging White sociologists to acknowledge the significance of racism in sociology and the emotions it engenders and to work to advance new personal and organizational anti-racist practices.